According to Baba : a collaborative oral history of Sudbury's Ukrainian Community - Zembrzycki, Stacey (Shared (Series), 2014)
"Dreams of steady employment in the mining sector led thousands of Ukrainian immigrants to northern Ontario in the early 1900s. As a child, historian Stacey Zembrzycki listened to her baba's stories about Sudbury's small but polarized community and what it was like growing up ethnic during the Depression.